The Impact of Breastfeeding on Mental Disorders in Children and Adults and the Role of Mother’s Mental Health: A Literature Review - Roguska, Zofia; Pernal, Maja; Mioduszewska, Joanna; Rot, Paweł; Poniewozik, Piotr; Dziuba, Natalia; Sim, Aleksandra; Zuzak, Andrzej Paweł; Poniewozik, Paweł; Grabowski, Krzysztof (Quality in Sport, 2026)
Background. Beyond providing nutrition to infants, breastfeeding plays a significant role in their physical, cognitive, and emotional development. An icreasing number of studies indicate that it may affect the child's mental health later in life through various mechanisms. The mental state of the mother can modify lactation and breast milk composition, potentially impacting infant development. Aim of the study. A review of literature on the impact of breastfeeding during infancy on mental disorders, including depression, anxiety disorders, autism spectrum disorders, and personality disorders, in childhood and adulthood, considering the mother's mental health as a potential modulating factor. Methodology. The review was conducted using PubMed and Google Scholar. Studies from 1998-2025 were analyzed. Results. Studies show breastfeeding supports cognitive development, reduces risk of mental disorders and promotes resilience to psychosocial stress. The mother's mental state and treatment may affect lactation and breast milk composition, influencing infant development. Conclusion. Breastfeeding may protect aspects of a child's mental health and cognitive development long-term. The mother's mental health influences breast milk composition and breastfeeding quality. Research remains inconclusive due to environmental and genetic factors, requiring more studies on breastfeeding's effects on cognition and mental health.